Entre paisagens, retratos e naturezas mortas : percursos metodológicos de/com Aby Warburg na pesquisa sobre arte em contextos da educação - Cerqueira, Fátima Nader Simões (2015)
This thesis defines the general objective around the theoretical investigation about the analysis and the understanding of artistic and cultural pratices reviewed, since the Panel 55, that was an integrant of the Atlas of Memory (Atlas Mnemosyne) of Aby Warbug, as methodology and tool that make possibilities of interpretation and significant associations between images of art and culture in order to imply that the investigative attitude and the experimentation of the researcher’s job make an ensemble of resources, instruments and procedures able to contribute to the formation of the involved at the system of education and learning about art. The attempt of understanding the operating modes of the iconological research achieves in the elaboration of an Experimental Panel that duplicates three works from the Panel 55 and associates to a new sequence of reproductions, starting from the concepts learned about the formula of páthos, symptom and survival of the images (since the Antiquity until the current days). For such, without the limitation of a prescriptive answer, the projection of this knowledge is sought by the association of the Warburg’s texts with the investigations of Georges Didi-Huberman about his legacy, in order to interpret how images regress, switch, invert and/or converge senses, creating new visual narratives that happens between mythological spaces, outdoor landscapes, pictures, still life and in the modern cities. So, it take off the lifting of hypothesis about the thought of the writer who died before to gather, register and publish, accurately, the reasons why he created correspondences and thematic, formal and gestural transformations between the associated works in the visual atlas.